Science and Technology for Sustainable Development Goals - Kiran , Vijay; Khatri , Vinod; Sangwan , Jasbir; Poonia , Ekta (Recent Developments in Science and Technology for Sustainable Future, 2024)
The imagination of sustainable development is not possible without science and technology. The developments in clean energy sector, pollution control and reduction of waste production is the key for sustainable development. Various methods have been developed to control the pollution which includes bioplastics, biofertilizers and biofuels. The chemically developed molecular organic framework (MOF) has been used to capture the excess CO2 in the environment. The methods of sustainable farming are explained in this chapter.